PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN WATTPAD TERHADAP KEMAMPUAN MENULIS TEKS ULASAN - Rosi Wanda Sari; Dida Firmansyah; Diena San Fauziya (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The idea of this research was initiated by the fact that there are still many students who have difficulty determining ideas and ideas in producing a review text by determining the structure and language of the review text. The Project-Based Learning learning model is used as an alternative solution to the learner-centred learning model, namely a learning model that uses projects or activities as a learning tool to achieve attitudes, knowledge and skills competencies. Therefore, this research was conducted to determine the learning process and the impact of the student's ability to write review texts. The purpose of the research is to determine the ability to write a review text of students using the Project-Based Learning learning model assisted by Wattpad. The research method used in this research is descriptive qualitative which only has one cycle of the treatment process, data collection and data processing. The results showed that 19 students got a high score, 6 students got an adequate score, and 1 student got a low score. The results of the study can be concluded that using the Project-Based Learning model can positively affect the learning process and improve students' skills in writing review texts.